(Re)Envisioning Childhoods With Mi’kmaw Literatures - Downey, Adrian M. (Journal of Childhood Studies)

(untitled) (Canadian Association for Young Children, 2022)
A generative reading of four recent children’s books by Mi’kmaw authors through Indigenous and posthumanist lenses, this article suggests that Indigenous children’s literature works at envisioning a “very old” future and highlights the counter-hegemonic potential of that future in the current moment. First, a reading of the Mi’kmaw mythopoetic tradition as speculative fiction is presented. Second, becoming-with Land is discussed as a radical pedagogical future. Third, the tensions between Indigenous and posthumanist theories are discussed, along with the generative potential of those tensions. The article concludes by highlighting the power of the very old futures (re)emergent from very old stories.